Analyzing Marketing Strategies to Enhance Consumer Purchase Decisions for Aluminum Products: Analisis Strategi Pemasaran Guna Meningkatkan Keputusan Pembelian Konsumen Terhadap Produk Aluminium - Mahputra, Arga Prahayasa; Purwanto, Nuri (Universitas Muhammadiyah Sidoarjo, 2023)
This research delves into the marketing strategies employed and factors influencing consumer purchase decisions concerning aluminium products within a Glass and Aluminium Furniture Store in Jombang city. Utilizing a qualitative approach with a phenomenological lens, this study engages 2 male and 1 female participants: the business owner, a customer, and an employee of the store. Through meticulous observation and unstructured interviews, valuable insights were gathered, revealing intricate connections between marketing tactics and consumer choices. The findings illuminate the paramount role of personalized marketing approaches in driving purchase decisions while shedding light on various psychological and sociocultural factors underpinning consumer behavior. This study enriches the understanding of consumer dynamics and offers practical implications for businesses seeking to enhance their market strategies. Highlights: Personalized Marketing Impact: The study reveals the significant influence of personalized marketing strategies on consumer purchase decisions, emphasizing tailored approaches in modern marketing landscapes. Psychosocial Factors: Intricate interplay of psychological and sociocultural factors unveils the nuanced drivers shaping consumer behavior, expanding the comprehension of decision-making dynamics. Business Implications: This research offers valuable insights for businesses aiming to optimize their marketing strategies, fostering a deeper understanding of consumer preferences and guiding effective decision-making processes. Keywords: Consumer Behavior, Marketing Strategies, Purchase Decisions, Aluminium Products, Qualitative Research.